Measuring the Locality Data Sets of Herbaria Festuca Species in England Using Google Earth - Shaikh Ali, Aseel (American Journal of Biology and Natural Sciences, 2025)
In this study, we used herbarium data to determine the locality data sets of Festuca species that are common in England and well represented in the University of Reading Herbarium (RNG). In this study, considerable number of specimens have been mainly utilized. We explored the localities at which herbarium specimens of Festuca species were collected and then the locality coordinates of these herbaria specimens were mapped using Google Earth. This study showed that most species Festuca species were concentrated abundantly in the south of England more than the north which agree with their recorded coordinates.